A ten-year histopathological study of generalised lymphadenopathy in India - G.C. Kamat (South African Family Practice)
Background: Lymphadenopathy is a rather common clinical finding in a primary healthcare setting, and may be due to inflammatory lesions and tumours. Correlation between clinical findings and laboratory data is essential in arriving at a diagnosis. This study was undertaken to study the histopathology of generalised lymphadenopathy in India, as well as the demographics of the study population.